High prevalence of obstructive lung disease in non-smoking farmers: The Irish farmers lung health study. (June 2016) - Cushen, Breda; Sulaiman, Imran; Donoghue, Noreen; Langan, Donna; Cahill, Tara; Nic Dhonncha, Eimear; Healy, Olivia; Keegan, Fiona; Browne, Mark; O'Regan, Anthony
Abstract: Background: Mortality rates within the Irish farming community are increasing, whilst that of the general population falls. The aim of this cross-sectional study was to determine the prevalence of respiratory disease amongst Irish farmers. Methods: All study participants were farming volunteers attending an agricultural exhibition. Data collected by questionnaire included baseline demographics, respiratory history, presence of respiratory symptoms and occupational exposures. Spirometry was performed on all participants. Results: Data from 372 farmers was analysed. The majority were male (76%) with median age of 55 years. 61% were never smokers. 13% were previously diagnosed with airway disease (Chronic Obstructive Pulmonary Disease(COPD)/Asthma/Inhaler use) with 14% reporting hayfever/allergies. Almost two-thirds reported one or more chronic respiratory symptom. Forty-four (12%) had obstructive spirometry using fixed FEV1 /FVC < 0.70 criterion and 29 (7.8%) using FEV1 /FVC < 5% lower limit of normal. The majority, two-thirds, were never smokers. Amongst never smokers with obstruction (13%), there was a significantly higher proportion with a prior diagnosis of airway disease and hayfever/allergies. There was no significant association between specific occupational exposures and obstruction. Conclusion: The majority of Irish farmers are never smokers. They have a high prevalence of respiratory symptoms. 13% of never smokers have airflow obstruction (FEV1 /FVC < 0.70). The presence of airflow obstruction is significantly associated with self-reported allergy history and prior airway disease. Further studies are needed to identify the workplace factors accounting for these findings. Highlights: This is the first cross-sectional study of the respiratory health of Irish farmers. 12% of Irish farmers had airflow obstruction on spirometry; 66% were never smokers. 62% of farmers reported one or more chronic respiratory symptom. Obstructive spirometry was associated with prior diagnosis of airways disease. No relationship was found between the presence of obstruction and the farming exposures assessed.